Content Analysis of Sixth Grade Science Textbooks in the Light of the Twenty-First Century Skills of Jordanian International Students in Public Schools - Alsalhi, Najeh Rajeh (Journal of International Students, 2023)
The study sought to determine the level of integration of twenty-first-century skills in the science curriculum for sixth-grade international students attending public schools in Jordan. To accomplish this objective, the study employed a descriptive analytical approach and utilised a content analysis tool that encompassed 46 sub-skills. The study sample was included in 30% of the content of the science book (in its first and second parts) for the sixth grade in Jordan, edition 2021-2022. The data was analysed using frequencies, percentages, and the arithmetic mean. The study findings revealed a decline in the inclusion of science courses for twenty-first century skills, with an average of 30.46% and a total of 533 repetitions. The study suggests reevaluating the science curriculum for sixth graders to incorporate twenty-first century skills in a manner that promotes integration and continuity.